Pengaruh Model Problem Based Learning (PBL) Terhadap Penguasaan Konsep dan Keterampilan Kerjasama Peserta Didik pada Matakuliah Telaah Biologi - Narsan, Vifty Octanarlia (Fakultas Tarbiyah dan Ilmu Keguruan UIN Jurai Siwo, Lampung, 2022)
The 21st century has brought various changes, including in the field of education so that global people are required to master various essential skills. One of the important skills is cooperation skills. The problem based learning model is a learning model that is in accordance with the demands of the 21st century. The Problem Based Learning (PBL) in this study was modified from Sufairoh (2016). The subjects of this study were 60 semester 6 students of the Tadris Biology study program at the Metro State Islamic Institute. The research method is pre-experiment and the one group pretest-posttest design. The data collection techniques used in this study were written tests for mastery of concepts, observation sheets for collaboration skills, and response questionnaires. The data collection instrument for mastering concepts was in the form of a written test in the form of a description totaling 10 items which were assessed using the assessment rubric of six indicators of mastery of concepts from bloom's taxonomy (Nurisnaeni, 2022). The cooperation skills are measured using an observation sheet containing 7 statements adopted from Mahanal (2014). Based on the research results, it can be concluded that learning using the problem based learning (PBL) model has the potential to increase students' mastery of concepts and collaborative skills in biology curriculum review courses. This is supported by student response data which gives a positive response to the Problem Based Learning (PBL) model.